Standardization of Nomenclature for Ocular Tuberculosis – Results of Collaborative Ocular Tuberculosis Study (COTS) Workshop. (30th September 2020) - Agrawal, Rupesh; Agarwal, Aniruddha; Jabs, Douglas A.; Kee, Aera; Testi, Ilaria; Mahajan, Sarakshi; McCluskey, Peter J.; Gupta, Amod; Palestine, Alan; Denniston, Alastair; Banker, Alay; Invernizzi, Alessandro; et al.
ABSTRACT: Purpose : To standardize a nomenclature system for defining clinical phenotypes, and outcome measures for reporting clinical and research data in patients with ocular tuberculosis (OTB). Methods : Uveitis experts initially administered and further deliberated the survey in an open meeting to determine and propose the preferred nomenclature for terms related to the OTB, terms describing the clinical phenotypes and treatment and reporting outcomes. Results : The group of experts reached a consensus on terming uveitis attributable to tuberculosis (TB) as tubercular uveitis. The working group introduced a SUN-compatible nomenclature that also defines disease "remission" and "cure", both of which are relevant for reporting treatment outcomes. Conclusion : A consensus nomenclature system has been adopted by a large group of international uveitis experts for OTB. The working group recommends the use of standardized nomenclature to prevent ambiguity in communication and to achieve the goal of spreading awareness of this blinding uveitis entity.